Enhanced Lipid Peroxidation and Platelet Activation as Potential Contributors to Increased Cardiovascular Risk in the Low‐HDL Phenotype. Issue 2 (4th April 2013) - Vazzana, Natale; Ganci, Antonina; Cefalù, Angelo Baldassare; Lattanzio, Stefano; Noto, Davide; Santoro, Nicole; Saggini, Raoul; Puccetti, Luca; Averna, Maurizio; Davì, Giovanni
Abstract : Background: Low high‐density lipoprotein (HDL) levels are major predictors of cardiovascular (CV) events, even in patients on statin treatment with low‐density lipoprotein (LDL) at target. In animal models HDLs protect LDL from oxidation and blunt platelet activation. Our study aimed to examine whether HDL levels are related to in vivo oxidative stress and platelet activation, as determinants of atherothrombosis. Methods and Results: Urinary 8‐iso‐PGF2α and 11‐dehydro‐TXB2, in vivo markers of oxidative stress and platelet activation, respectively, were measured in 65 coronary heart disease (CHD) normocholesterolemic patients with HDL ≤35 mg/dL, and in 47 CHD patients with HDL >35 mg/dL. The 2 eicosanoids were also measured before and after an intensive exercise program in sedentary people (n=18) and before and after fenofibrate treatment in otherwise healthy subjects with low HDL (n=10). Patients with HDL ≤35 mg/dL showed significantly higher urinary 8‐iso‐PGF2α (median [25th to 75th percentiles]: 289 [189 to 380] versus 216 [171 to 321] pg/mg creatinine, P =0.019) and 11‐dehydro‐TXB2 (563 [421 to 767] versus 372 [249 to 465] pg/mg creatinine, P =0.0001) than patients with higher HDL. A direct correlation was found between urinary 8‐iso‐PGF2α and 11‐dehydro‐TXB2 in the entire group of patients (ρ=0.77, P <0.0001). HDL levels were inversely related to both 8‐iso‐PGF2α (ρ=−0.32, P =0.001) and 11‐dehydro‐TXB2 (ρ=−0.52, P <0.0001). On multiple regression, only 8‐iso‐PGF2α (β=0.68, P <0.0001) and HDL level (β=−0.29, P <0.0001) were associated with urinary 11‐dehydro‐TXB2 excretion, independent of sex, age, smoking, hypertension, diabetes, previous myocardial infarction, total cholesterol, LDL, and triglycerides. Both intensive exercise and fenofibrate treatment significantly reduced the 2 eicosanoids in healthy subjects, in parallel with an HDL increase. Conclusions: A low HDL phenotype, both in CHD patients and in healthy subjects, is associated with increased lipid peroxidation and platelet activation. These data provide novel insight into the mechanisms linking low HDL with increased CV risk.